Metastatic brain tumor secondary to pancreatic adenocarcinoma - Pastorello, Julia; Lando, Emanuela; Ractz Bueno, Marina; dos Santos do Amaral, Camila (Brazilian Journal of Case Reports, 2022)
Pancreatic neoplasm is represented by the subtype Adenocarcinoma in 90% to 95% of cases, characterized by the high lethality rate of its presentations; however, cases of progression in the brain site are manifested in only 0.1% to 0.3% of all the cases. The present study aims to report a rare case of a patient undergoing treatment for pancreatic cancer, which had a median overall survival significantly higher than the median time related to such neoplasm, and during the final evolution of the disease progression, an unusual associated with symptomatic brain metastatic activity, was evidenced, thus we correlated the current medical literary data to the events presented by the reported patient. Thus, the reported case becomes of extreme clinical relevance for the study of modern clinical oncology.